(untitled) (Al Dzahab, 2025)
Purpose: This study aims to analyze the effect of digital financial literacy on business sustainability and the quality of financial reporting of MSMEs in Manado City. Design/Methodology/Approach: The research employs a causal associative method with a quantitative approach, involving 87 MSME actors in Manado City selected through purposive sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling with Partial Least Squares (PLS-SEM) via SmartPLS version 4.0. Findings: The hypothesis testing shows that digital financial literacy has a positive and significant effect on both business sustainability and the quality of MSMEs’ financial reporting. The findings reveal that the impact of digital financial literacy on financial reporting quality is stronger than its effect on business sustainability, indicating that enhancing digital financial literacy is more effective in improving the quality of financial reporting than in sustaining business operations as a whole. Research Implications: Strengthening digital financial literacy programs is essential for MSMEs to support digital transformation and enhance business competitiveness in the digital economy era.